Evaluation of Some New Cytokines in Rheumatoid Arthritis - Omran, Raghda H.; Ahmed, Zahra’a A.; Alrawi, Aymen A. (Journal of the Faculty of Medicine Baghdad, 2022)
Background: Cytokines have an essential contribution to the inflammatory response and the development of chronic inflammation. Therefore, it has a pivotal role in the pathogenesis of rheumatoid arthritis (RA). Interleukins are closely related to RA, and the exact role of some interleukins in the pathogenesis of RA is not yet known. Objectives: To evaluate the levels of interleukins and their ratio, since the levels of interleukins 35 and 39 in RA patients have not yet been determined in Iraq. Patients and methods: An ELISA (enzyme-linked immunosorbent assay) was used to measure the levels of interleukins in the blood of 56 patients with RA and 44 healthy volunteers who were enrolled in the study from November 2021 to March 2022. Results: The serum levels of IL-39 in the RA patient groups were significantly higher than in the control groups (p = 0.043). In contrast, the level of IL-35 was slightly higher in RA patients but not by significantly different values (p = 0.055). The cytokine ratio, IL-39/IL-35, was the same for the groups, and there were no significant differences when comparing patients to controls (14.30 ± 1.47 vs. 13.18 ± 0.71). In addition, IL-39 concentration levels were significantly higher in RA patients under therapy than in RA patients with a first diagnosis and without therapy. Conclusion: The study concluded the crucial role of pro-inflammatory and anti-inflammatory cytokines in the progression of RA.